Ejecución del gasto en inversión y su relación con el gasto total en la Municipalidad de Torres Causana periodo 2018-2022 - Pinto Bautista, Luis Octavio (2025)
Investment spending in municipalities in the interior of the country plays a fundamental role in regional development. However, the Peruvian Institute of Economy (2023) mentions that during the municipal period 2015-2018, approximately 27% of municipalities executed less than 60% of their investment budget. This study aims to identify the relationship between investment spending execution and total spending in the municipality of Torres Causana during the period 2018-2022. Using a quantitative approach with an observational and non-experimental correlational study, the results reveal that total investment spending is not significantly related to the municipality's total spending, suggesting a management disconnected from the entity's overall budget. However, investment in goods shows a strong positive and significant correlation with total spending (Pearson correlation = 0.921, p = 0.026), indicating efficient and effective management in this area. No significant correlation was found between total spending and infrastructure investments, evidencing a lack of clear and coherent policy in this area. Additionally, the lack of significant relationship in investments in intangibles and other financial assets highlights the urgent need to improve management in this area to ensure more effective use of resources. These findings underscore the importance of strengthening the planning, execution, and evaluation of investment projects in infrastructure and intangibles. Furthermore, it is essential to diversify and optimize investment management to maximize its positive impact on the development and well-being of the Torres Causana community.